(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
The review of image appreciation methods since the 15th century shows that all educational theories, even the most recent, separate creation and appreciation situations. To give coherence to artistic education, we propose to define creation situations and appreciation situations, according to the same logic specific to the arts: “artistic reflection” produces a “creative and aesthetic judgment”, specific to artists but also to contemporary art critics or other professionals in the arts field. In this article, we propose a redesign of the six dialogic methods identified in current educational theories, to adapt them to artistic education, by limiting ourselves to apperception, the first step in an appreciation process.